Features of Infusion Therapy in Critically Ill Children - V.I. Snisar (Zaslavsky O.Yu., 2015)
This review shows that the appointment of infusion therapy on generally accepted recommendations of M.A. Holliday, M.E. Segar often leads to hyponatremia and significant complications. Injected volume of fluid in the critical ill children cannot accurately be determined. It depends on many factors: the diseases severity in child, used methods of intensive care. Critical state, pain, administration of a number of drugs stimulate increased secretion of antidiuretic hormone. This restricts the release of water with urine, especially in a situation when administration of the electrolyte-free liquid results in hyponatremia and a positive water balance. What is the ideal solution during infusion therapy in children: a hypotonic fluid or isotonic one? Until now the debate continues while the use of hypotonic solutions is yet widespread enough. However, this leads to hyponatremia and increases the risk of adverse neurological complications in critically ill children. Therefore, the routine use of hypotonic solutions should be reconsidered. In all cases, a minimum monitoring of water balance and electrolyte levels in the blood plasma should be provided.